The Predictive Role of Lactate in the Emergency Department in Patients with Severe Dyspnea - Maciej Niczewski; Szymon Gawęda; Paulina Kluszczyk; Mikołaj Rycerski; Daria Syguła; Anna Danel; Szymon Szmigiel; Konrad Mendrala; Aleksandra Oraczewska; Czarosław Kijonka; Monika Nowicka; Michał Wita; et al. (Emergency Medicine International)
Objective. An accurate identification of patients at the need for prioritized diagnostics and care are crucial in the emergency department (ED). Blood gas (BG) analysis is a widely available laboratory test, which allows to measure vital parameters, including markers of ventilation and perfusion. The aim of our analysis was to assess whether blood gas parameters in patients with dyspnea at an increased risk of respiratory failure admitted to the ED can predict short-term outcomes. Methods. The study group eventually consisted of 108 patients, with available BG analysis. The clinical and laboratory parameters were retrospectively evaluated, and three groups were distinguished—arterial blood gas (ABG), venous blood gas (VBG), and mixed blood gas. The primary endpoint was short-term, all-cause mortality during the follow-up of median (quartile 1–quartile 3) 2 (1–4) months. The independent risk factors for mortality that could be obtained from blood gas sampling were evaluated. Results. The short-term mortality was 35.2% (38/108). Patients who died were more frequently initially assigned to the red triage risk group, more burdened with comorbidities, and the median SpO2 on admission was significantly lower than in patients who survived the follow-up period. In the multivariable analysis, lactate was the strongest independent predictor of death, with 1 mmol/L increasing all-cause mortality by 58% in ABG (95% CI: 1.01–2.47), by 80% in VBG (95% CI: 1.13–2.88), and by 68% in the mixed blood gas analysis (95% CI: 1.22–2.31), what remained significant in VBG and mixed group after correction for base excess. In each group, pH, pO2, and pCO2 did not predict short-term mortality. Conclusions. In patients admitted to the ED due to dyspnea, at risk of respiratory failure, lactate levels in arterial, venous, and mixed blood samples are independent predictors of short-term mortality.